Successes in African agriculture: results of an expert survey - Gabre-Madhin, Eleni Zaude; Haggblade, Steven (International Food Policy Research Institute, 2001)
A broad survey of expert opinions in was conducted July 2000 to February 2001, with over 1500 questionnaires mailed to experts within and outside Africa on nominations of African agricultural success stories and the rationale for selection of success stories, and factors determining success.